How does diabetic peripheral neuropathy impact patients' burden of illness and the economy? A retrospective study in Beijing, China - Pan, Qi; Fei, Sijia; Zhang, Lina; Chen, Huan; Luo, Jingyi; Wang, Weihao; Xiao, Fei; Guo, Lixin (Frontiers in Public Health, 2023)
Objective Diabetic peripheral neuropathy (DPN) causes significant illness in patients and has a negative impact on the economy. The objective of this study is to evaluate the cost and quantity of anti-diabetic drugs needed by patients with or without DPN, as well as their variation trends in Beijing between 2016 and 2018. Methods This observational cross-sectional study used data on diabetic patients with outpatient medication records obtained from Beijing Medical Insurance from 2016 to 2018. The medications, comorbidities, diabetes-related complications, treatment strategies, and costs of drug treatment were compared between DPN patients and non-DPN patients. Results Of the 28,53,036 diabetic patients included in the study, 3,75,216 (13.15%) had DPN and 1,87,710 (50.03%) of the DPN patients were women. Compared with non-DPN patients, DPN patients used more mediations (4.7 ± 2.47 vs. 3.77 ± 2.32, p < 0.0001, in 2018) to treat related complications and comorbidities (2.03 ± 1.2 vs. 1.71 ± 1.05; 2.68 ± 1.93 vs. 2.06 ± 1.86, p < 0.0001, respectively, in 2018). The total annual costs of drug treatment were higher in DPN patients than in non-DPN patients (¥12583.25 ± 10671.48 vs. ¥9810.91 ± 9234.14, p < 0.0001, in 2018). The usage of DDP4i increased from 2.55 to 6.63% in non-DPN patients and from 4.45 to 10.09% in DPN patients from 2017 to 2018. Conclusions The number of comorbidities, diabetic complications, medications, and annual drug treatment costs were greater in DPN patients than in non-DPN patients.